Party tourism impacts on local stakeholders. Issue 2 (3rd April 2022) - Mach, Leon; Connors, James; Lechtman, Bronya; Plante, Sam; Uerling, Calle
ABSTRACT: This paper presents residents' perspectives on the impacts of party tourism in Bocas del Toro, Panama. Quantitative and qualitative data were gathered from local stakeholders via surveys (n = 193) and semi-structured interviews (n = 23). Survey results demonstrate that party tourism's economic benefits do not outweigh the social costs, which was surprising given the early stage of tourism development. Findings also suggest that older generations and those uninvolved in the industry perceived party tourism impacts more negatively than younger and economically reliant respondents. Semi-structured interviews elaborated on resident perspectives and lead to recommended pathways for mitigating negative party tourism impacts and also validate the need for a better understanding of the role of party tourism in destination development.